Genotype Profiles of Actinobacillus pleuropneumoniae Isolated from Pigs in Vojvodina, Serbia - Kojić, Kosta; Stevančević, Ognjen; Savić, Božidar; Stojanac, Nenad; Davidov, Ivana; Spasojević, Jovan; Cincović, Marko (Acta Scientiae Veterinariae, 2022)
Background: Actinobacillus pleuropneumoniae (A. pleuropneumoniae) is one of the most important bacterial respiratory pathogens. It is the only etiological agent of porcine pleuropneumonia (PPP) or it appears as a secondary bacterial infection in the swine respiratory disease complex (PRDC). In Serbia, apart from the identification of serotype 2, no tests have been performed to establish the presence of other A. pleuropneumoniae serotypes in the pig population. The aim of this study was to perform genotyping of A. pleuropneumoniae isolates originating from pig farms in Serbia by apx genes and using multiplex polymerase chain reaction (mPCR). Materials, Methods & Results: Isolates of A. pleuropneumoniae examined in this study were obtained from lungs with macroscopically visible alterations characteristic of a A. pleuropneumoniae. A total of 46 isolates were examined. They were extracted from the lung tissue samples of pig carcasses from 9 farms across different parts of Serbia. Genotyping of isolates was performed in the previously described manner. Briefly, 5 pairs of oligonucleotide primers were used for amplification of 4 different apx genes which encode synthesis of exotoxins (ApxI , ApxII , ApxIII i ApxIV) characteristic for all A. pleuropneumoniae serotypes and biovars. Amplification of appropriate genome parts was performed with a reaction chain polymerase (PCR) in multiplex (m) format using appropriate diagnostic kits to extract DNA from bacteria and perform mPCR reaction. The results of genotyping of 46 isolates of A. pleuropneumoniae indicate the existence of a large number of different serotypes of A. pleuropneumoniae on the studied farms or that different serotypes of this microorganism circulate in the pig population in Serbia. In addition to the detection of dominant serotype 2, which was established on 7 farms, of which in 4 farms it was the only detected serotype, in the examined pig population the presence of serotypes 3, 5, 6, 7 and 9 was also found. Furthermore, the presence of 2 different serotypes of A. Pleuropneumoniae was also detected on 3 farms; on the first farm serotypes 2 and 3, on the second farm serotypes 2 and 6, and on the third farm serotypes 2 and 7. Discussion: Although the research was done with a relatively small number of isolates of A. pleuropneumoniae, comparing the obtained results with the results on the presence and prevalence of appropriate serotypes from other countries, we concluded that there is significant diversity of this pathogen in the pig population in farms of Serbia. Detection of different serotypes of A. pleuropneumoniae in the pig population and the presence of several different serotypes on 1 farm was established for the very first time in Serbia. All isolates from our study can be characterized as highly virulent, considering that the clinical symptoms, pathological findings and the results of bacteriological examination indicated A. pleuropneumoniae to be the cause of animal death. Like in the neighbouring countries, the strongly pathogenic serotype 9 and the less pathogenic serotype 2 are the most frequently identified causative agents of porcine pleuropneumonia in the Autonomous Province of Vojvodina, Republic of Serbia. The necessity to establish the presence of all A. pleuropneumoniae serotypes in the pig population, and in particular to determine the presence of different serotypes on individual farms, is crucial for several reasons: making a definitive diagnosis; development of prophylactic strategies for medicines; implementation of immunoprophylactic vaccination. Keywords: swine, porcine pleuropneumonia, PPP, serovar 2, serotype, lung, PCR.